PENGARUH KOMPETENSI GURU DAN LINGKUNGAN TEMAN SEBAYA TERHADAP PRESTASI BELAJAR SISWA MATA PELAJARAN KORESPONDENSI KELAS X ADMINISTRASI PERKANTORAN SMK NEGERI 1 SUKOHARJO - Romadhoni Setyo Nugroho; Djoko Santoso; Patni Ninghardjanti (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2018)
This research aims to identify: 1) The influence of Peer Group to Correspondence Achievement Students Of X Office Administration Class At SMK Negeri 1 Sukoharjo Academic Year 2016/2017, 2) The influence of Teacher Competence to Correspondence Achievement Students Of X Office Administration Class At SMK Negeri 1 Sukoharjo Academic Year 2016/2017, 3) The influence of Teacher Competence and Peer Group to Correspondence Achievement Students Of X Office Administration Class At SMK Negeri 1 Sukoharjo Academic Year 2016/2017. This research was an ex-post facto with quantitative approach. Research result: 1) Have a positive influence and significant of Teacher Competence to Correspondence Achievement by = 0,441; = = 0,185; tcount 4,449; ttable 1, 99 with significantly of 5%. 2) Have a positive influence and significant of Peer Group to Correspondence Achievement by = 0,425; = 0,171; tcount 4,300; ttable 1, 99 with significantly of 5%. 3) Have a positive influence and significant of teacher competence and Peer Group to Correspondence Achievement by = 0,486; = 0,218; Fcount 12,849; Ftable 3,11, with significantly of 5%.